CROI 2019: Advances in HIV Prevention and Plans to End The Epidemic - Buchbinder, Susan P. (Top Antivir Med, 2019)
At the 2019 Conference on Retroviruses and Opportunistic Infections (CROI), a plan for ending the HIV epidemic in the United States was presented. More rapid HIV diagnosis and treatment is a key component needed nationwide. In international settings, substantial scale up of HIV testing and treatment has led to substantial declines in HIV incidence. U=U (undetectable equals untransmittable) is a powerful concept that can reduce stigma and encourage engagement in testing and care, but raises a number of clinical questions. HIV testing remains a gateway to HIV prevention and treatment, and innovative testing strategies, including HIV self-testing, show promise. Opioid overdose deaths are on the rise, highlighting the need for comprehensive prevention efforts. Molecular data are being used to identify rapidly growing clusters of infections for intervention. Rates of sexually transmitted infections have increased substantially in recent years. A new preexposure prophylaxis (PrEP) combination, tenofovir alafenamide/emtricitabine (FTC), was demonstrated to be non inferior to tenofovir disoproxil fumarate/FTC, with improved bone and renal safety. PrEP uptake is increasing globally, but use is lower in several populations, including African Americans, cis- and transgender women, and youth. Same-day PrEP initiations are a promising approach to increasing access, but PrEP discontinuations remain a challenge.